Truth Telling as an Element of Ethical Behaviour and Professional Commitment in Dentistry: A Case Study Assessing Non-Disclosure Action - Sadighpour, Leyla; Anderson, Greg (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2022)
Being truthful with patients is a critical foundation of the doctor-patient relationship and is fundamental to development of trust. A professional commitment to truth telling may sometimes contradict other principles of bioethics, which may challenge decision-making for the doctor and/or the treatment team. Practitioners may fail to address all ethical or legal aspects of a case and therefore make inappropriate decisions.